1960
DOI: 10.1212/wnl.10.2.107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of serotonin in migraine patients

Abstract: LITTLE is known of the factors that predispose to migraine or the biochemical events that initiate the disturbances characteristic of this condition. Earlier studies by Marcussen and Wolffl have shown that an initial phase of vasoconstriction is responsible for the prodroma1 symptoms, while the pain follows a marked distention of cranial vessels that are temporarily hypotonic. They also have presented certain evidence which presumably indicates that a pain threshold-lowering substance renders the distention of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
4

Year Published

1961
1961
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(73 citation statements)
references
References 1 publication
3
66
0
4
Order By: Relevance
“…With the first class of MAO inhibitors, uncontrolled studies, lacking a comparison, were initiated to determine whether these drugs could be of use in the treatment of migraine and tension type headaches (Dalsgaard-Neilson, 1962;Michelacci & Franchi, 1962). These studies were based on the hypothesis that these diseases are caused by low levels of serotonin in the brain which subsequently led to the development of triptans to act as agonists on the serotonin receptors (Kimball, Friedman & Vallejo, 1960;Saxena & Ferrari, 1992). Phenelzine was considered a powerful medication for migraines and daily headaches.…”
Section: Migraine and Tension Type Headachementioning
confidence: 99%
“…With the first class of MAO inhibitors, uncontrolled studies, lacking a comparison, were initiated to determine whether these drugs could be of use in the treatment of migraine and tension type headaches (Dalsgaard-Neilson, 1962;Michelacci & Franchi, 1962). These studies were based on the hypothesis that these diseases are caused by low levels of serotonin in the brain which subsequently led to the development of triptans to act as agonists on the serotonin receptors (Kimball, Friedman & Vallejo, 1960;Saxena & Ferrari, 1992). Phenelzine was considered a powerful medication for migraines and daily headaches.…”
Section: Migraine and Tension Type Headachementioning
confidence: 99%
“…In this respect, (a) there is an elevation of urinary excretion of 5-hydroxyindole acetic acid, the major metabolite of 5-HT, during migraine attacks (Curran et al 1965); (b) platelet 5-HT levels were found to drop rapidly during the onset of a migraine attack (Anthony et al 1967); (c) reserpine, which depletes 5-HT (and noradrenaline), precipitates migraine attacks (Carroll and Hilton 1974); intravenous injection of 5-HT reduces headache intensity in migraineurs (Anthony et al 1967;Kimball et al 1960). …”
Section: -Ht Receptorsmentioning
confidence: 99%
“…Arteriovenous shunting has been implicated in the pathophysiology of migraine where profound vasodilatation in these large shunt vessels may lead to a reverse 'steal' (Heyck, 1969;Saxena, 1978;. Indeed anti-migraine drugs, particularly the ergot alkaloids effective in the treatment of individual attacks (Johnston & Saxena, 1978;Schamhardt et al, 1979;Spierings & Saxena, 1980), as well as 5-HT (Saxena & Verdouw, 1982) which may also alleviate migraine attacks (Kimball et al, 1960;Lance, 1982), cause an 'active' constriction of AVAs. Though the overall effect of nimodipine on the distribution of carotid artery blood flow into nutrient and nonnutrient fractions qualitatively resembles that of the above drugs, nimodipine is less efficacious and, as discussed above, has a 'passive' effect on AVAs.…”
Section: Carotid Haemodynamicsmentioning
confidence: 99%